Learning curve and short-term outcomes of modularized LADG for advanced gastric cancer: A retrospective study. Issue 10 (March 2019) - Liao, Gang; Wang, Ziwei; Li, Hui; Min, Jiang; Zhong, Jinkun; Mariella, Sandrie; Qian, Kun; Zhang, Wei
Abstract : Abstract: Laparoscopy-assisted distal gastrectomy (LADG) is a complicated procedure. To reduce the difficulty of the operation and standardize the surgical procedure, we explored a new operation mode, which we termed modularized LADG (MLADG). To further extend the new operation mode, we conducted this study to evaluate the short-term outcomes of MLADG for advanced gastric cancer, and determine the learning curve. Data from 100 consecutive patients who received LADG between October 2016 and October 2017 were retrospectively analyzed. Short-term outcomes, such as operation time and intraoperative blood loss, were evaluated, and the learning curve was calculated. For MLADG, the mean operation time was 168.2 ± 13.0 minutes, the mean intraoperative blood loss was 93.6 ± 29.1 ml, the mean number of harvested lymph nodes was 28.6 ± 4.2, and conversion to open surgery occurred in only 1 case. In addition, MLADG had an acceptable postoperative complication incidence and fast postoperative recovery. After the first 20 cases, the operation skill reached a mature and stable level. Our results indicate that MLADG is an oncologically feasible and technically safe surgical procedure. For the trainees with rich experience in open distal gastrectomy, the learning curve is considered to be completed after 20 MLADG cases.